Peripheral neurotoxicity induced by albumin-bound paclitaxel: a case report - Li, Xiaojing; Wu, Liuting; Bai, Dunyao (Frontiers in Oncology, 2024)
BackgroundDespite its excellent therapeutic efficacy, albumin-bound paclitaxel often leads to peripheral neurotoxicity, significantly affecting patients’ quality of life. This study reported a case of non-small cell lung cancer (NSCLC) with peripheral neurotoxicity induced by albumin-bound paclitaxel.Case presentationA 70-year-old male was admitted to the Hubei Cancer Hospital complaining of left-side limb weakness and numbness for one month following the first cycle of albumin paclitaxel plus cisplatin plus tislelizumab regimen for the right-side NSCLC in December 2021. Chest CT displayed a soft tissue density mass in the apical segment of the right upper lung lobe (5.5×4.9 cm2). Immunohistochemistry results and CT-guided percutaneous lung biopsy confirmed NSCLC stage cT3NXMX. The pain and numbness in both feet were alleviated after the first cycle of this regimen of liposomal paclitaxel 240 mg plus cisplatin 90 mg plus tislelizumab 200 mg. After four treatment cycles, the tumor treatment was evaluated as partial response (PR), and the tumor lesion became 2.9×2.7 cm2.ConclusionThe regimen containing liposomal paclitaxel, cisplatin, and tislelizumab alleviated the symptoms of peripheral neurotoxicity induced by albumin-bound paclitaxel in an NSCLC case, which may be a potential therapeutic option.